A decade of change in breastfeeding in China's far north-west - Xiao Cuiqin; Binns Colin W; Liu Xiaoxian; Xu Fenglian; Wu Jing; Lee Andy H (BMC, 2006)
Abstract Background There have been considerable changes in breastfeeding practices in China over the past forty years. However China is a very large country, and breastfeeding rates in different parts of China vary considerably. The objective of this paper is to identify and compare breastfeeding types and rates between 1994-1996 and 2003-2004 in Shihezi, Xinjiang Uygur Autonomous Region, PR China. Methods In 1994-1996, a study of breastfeeding (n = 2197) was undertaken in Shihezi, Xinjiang, PR China. A decade later in 2003-2004, a longitudinal study (n = 545) of infant feeding practices was undertaken in the same area. Results The 'any breastfeeding' rates at 1, 4 and 6 months were 94%, 82% and 78% respectively in the early 1990s. A decade later, breastfeeding at 1 month was lower, but rates at 4 and 6 months remained the same. In 2004 the 'full breastfeeding' rate at one month was significantly higher (57%) than a decade earlier (38%), but after 3 months there was a rapid decline. This reflected a shift in the way complementary foods are introduced: the initial introduction was later, but by a higher proportion of mothers. Conclusion The rate of breastfeeding at one month is significantly lower in 2003-2004 when compared to 1994-1996. The 'full breastfeeding' rates were initially higher, but after 3 months were then lower. The Chinese national breastfeeding targets were not reached in either period of the study. These studies show the need to further promote full or exclusive breastfeeding and further longitudinal studies are necessary to provide the detailed knowledge about risk factors required for health promotion programs.